ANALISIS KINERJA STRUKTUR GEDUNG FT E.03 UNIVERSITAS TIDAR TERHADAP GAYA GESER DASAR SEISMIK DENGAN METODE DINAMIK RESPONS SPEKTRUM - Fajar Setianto; Yudhi Arnandha; Lalu Samsul Aswadi (Matriks Teknik Sipil, 2025)
According to BMKG earthquakes that occurred in Indonesia in 2023 with a minimum magnitude of 5.0 with various depths of 243 times. This condition is due to the geographical location of Indonesia is located between three tectonic plates so prone to earthquakes. Therefore, preventive measures are needed to reduce the impact of earthquakes on the failure of building structures. Faculty Of Engineering Building E.03 Tidar University is planned for 2015 with earthquake resistance Planning Standards in accordance with SNI 1726:2012. The planning standard has been revised to SNI 1726: 2019. Therefore, re-analysis according to the latest standards is required to determine the safety of the structure. Analysis using dynamic spectral response method. The maximum deviation of the roof ring beam in the x direction is 49.52 mm and the y direction is 61.25 mm. The largest shear force in the x direction is 7113.99 kN and the y direction is 6971.90 kN. The structural performance level is immediate occupancy with a roof drift ratio in the x direction of 0.0024 and y direction of 0.0030. Faculty of Engineering Building E.03 Tidar University has the ability to withstand earthquake forces with no damage to the structure. Keywords: dynamic response spectrum; seismic base shear force; structural performance level